Boosting γδ T cell-mediated antibody-dependent cellular cytotoxicity by PD-1 blockade in follicular lymphoma. (4th March 2019) - Rossi, Cédric; Gravelle, Pauline; Decaup, Emilie; Bordenave, Julie; Poupot, Mary; Tosolini, Marie; Franchini, Don-Marc; Laurent, Camille; Morin, Renaud; Lagarde, Jean-Michel; Ysebaert, Loïc; Ligat, Laetitia; et al.
ABSTRACT: Follicular lymphoma (FL) is a common non Hodgkin's lymphoma subtype in which immune escape mechanisms are implicated in resistance to chemo-immunotherapy. Although molecular studies point to qualitative and quantitative deregulation of immune checkpoints, in depth cellular analysis of FL immune escape is lacking. Here, by functional assays and in silico analyses we show that a subset of FL patients displays a 'high' immune escape phenotype. These FL cases are characterized by abundant infiltration of PD1 + CD16 + TCRVγ9Vδ2 γδ T lymphocytes. In a 3D co-culture assay (MALC), γδ T cells mediate both direct and indirect (ADCC in the presence of anti-CD20 mAbs) cytolytic activity against FL cell aggregates. Importantly, PD-1, which is expressed by most FL-infiltrating γδ T lymphocytes with ADCC capacity, impairs these functions. In conclusion, we identify a PD1-regulated γδ T cell cytolytic immune component in FL. Our data provide a treatment rational by PD-1 blockade aimed at boosting γδ T cell anti-tumor functions in FL.